Determination of Digital Accounting Factors to Increase MSMEs Income - Maryanto, Maryanto; Ayu Esteka Sari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the factors that affect the adoption of digital accounting and its impact on the increase in income of Micro, Small, and Medium Enterprises (MSMEs). Using quantitative methods and the Structural Equation Modeling (SEM) approach through AMOS software, this study identifies three main factors that play a role in the adoption of digital accounting, namely technology, internal organization, and regulation. The results of the analysis show that internal organizational factors have the greatest influence on the implementation of digital accounting, followed by regulations and technology. The tested research model met the Goodness of Fit criteria, with an R² value of 0.664, which shows that 66.4% variability in digital accounting adoption can be explained by these three factors. The synergy between MSMEs, the government, and technology developers is very important to accelerate digital transformation and increase the competitiveness of MSMEs in the digital economy era.